Australian Banking System Resilience : What Should Be Expected Looking Forward? An International Perspective - Bologna, Pierluigi (IMF Working Papers; Working Paper ;, 2010)
This paper reviews Australian banks' performance from an international perspective, with a focus on changes in capital and liquidity risk. The paper analyses the extent of any vulnerability that might arise from a potential deterioration in the funding markets and discusses whether liquidity rules, such as those being considered by the Basel Committee on Banking Supervision, may help reduce banks' liquidity risks and improve financial stability.